Immunomodulatory Role of Mesenchymal Stem Cell Therapy in Vascularized Composite Allotransplantation. (16th October 2016) - Heyes, Richard; Iarocci, Andrew; Tchoukalova, Yourka; Lott, David G.
Abstract : This review aims to summarize contemporary evidence of the in vitro and in vivo immunomodulatory effects of mesenchymal stem cells (MSCs) in promoting vascularized composite allotransplant (VCA) tolerance. An extensive literature review was performed to identify pertinent articles of merit. Prospective preclinical trials in mammal subjects receiving VCA (or skin allograft) with administration of MSCs were reviewed. Prospective clinical trials with intravascular delivery of MSCs in human populations undergoing solid organ transplant were also identified and reviewed. Sixteen preclinical studies are included. Eleven studies compared MSC monotherapy to no therapy; of these, ten reported improved graft survival, which was statistically significantly prolonged in eight. Eight studies analyzed allograft survival with MSC therapy as an adjunct to proven immunosuppressive regimens. In these studies, daily immunosuppression was transiently delivered and then stopped. In all studies, treatment-free graft survival was statistically significantly prolonged in animals that received MSC therapy. MSCs have been safely administered clinically and their use in renal transplant clinical trials provides evidence that they improve allograft transplant tolerance in clinical practice. There is potential for MSC induction therapy to overcome many of the obstacles to widespread VCA in clinical practice. Preclinical studies are needed before MSC-induced VCA tolerance becomes a clinical reality.